Caracterização ultraestrutural da cartilagem articular em modelos experimentais de osteoartrite em camundongos - Porto, Fernanda Maria Aragão Ximenes (2018)
Osteoarthritis (OA) is characterized by progressive deterioration of articular cartilage accompanied by changes in surrounding tissues. Surgical methods for OA induction, such as anterior cruciate ligament transection (ACLT) and destabilization of the medial meniscus (DMM) promote histological changes such as degeneration of cartilage at four weeks after induction. This study characterized the ultrastructural injuriesin articular cartilage in OA two models. Therefore, Swiss mice underwent DMM (n = 15) or ACLT (n = 15), and euthanized under anesthesia, in times of 3, 7 or 14 days postsurgery. Sham group (n = 15) was submitted to skin incision and breaking joint capsule, followed by suturing the tissues. After euthanasia, knee joints were dissected and prepared for analysis by optical microscopy (OM) and scanning electron microscopy (SEM). Samples of synovium and articular cartilage were stained with HE and Osafranin for histological analysis. Images obtained by SEM were examined for articular cartilage thickness, number of layers of chondrocytes, roughness coefficient and the degree of cartilage degradation, and surface microtopography. The histopathological analysis showed increasing trend synovial scores indicating inflammatory pattern over the experimental period in the groups submitted to DMM and ACLT. It was not possible to observe changes in the articular cartilage through the OM at all groups. The images obtained by SEM revealed loss of articular continuity, cracks and detachment of the joint surface at ACLT and DMM groups at 14 days. In the same period there was a decrease in tibial cartilage thickness in DMM and ACLT groups. There was a decrease in the number of layers of chondrocytes in the femur and tibia in the DMM group compared to the sham group in all experimental days (p <0.05). After two weeks, the roughness coefficient in the tibia and femur increased in the DMM group, making the surface microtopography more heterogeneous as compared to the sham group. Therefore, early OA lesions are detectable by SEM at times of 7 and 14 days in the ACLT models and DMM. These findings were not observed by OM.